2019
DOI: 10.1186/s12879-019-3729-5
|View full text |Cite
|
Sign up to set email alerts
|

A case-crossover analysis of the impact of weather on primary cases of Middle East respiratory syndrome

Abstract: BackgroundMiddle East respiratory syndrome coronavirus (MERS-CoV) is endemic in dromedary camels in the Arabian Peninsula, and zoonotic transmission to people is a sporadic event. In the absence of epidemiological data on the reservoir species, patterns of zoonotic transmission have largely been approximated from primary human cases. This study aimed to identify meteorological factors that may increase the risk of primary MERS infections in humans.MethodsA case-crossover design was used to identify association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 28 publications
4
88
3
1
Order By: Relevance
“…A one • C increase in monthly average temperature correlated with increasing the monthly incidence of MERS-CoV infection by 5.4%. This finding contradicts the Gardner et al study, where they reported low temperatures associated with high risk in primary MERS-CoV infections [9]. However, our report was in agreement with the Alghamdi et al study where they found that high temperatures enhance the spread of MERS-CoV in the population [11].…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…A one • C increase in monthly average temperature correlated with increasing the monthly incidence of MERS-CoV infection by 5.4%. This finding contradicts the Gardner et al study, where they reported low temperatures associated with high risk in primary MERS-CoV infections [9]. However, our report was in agreement with the Alghamdi et al study where they found that high temperatures enhance the spread of MERS-CoV in the population [11].…”
Section: Discussioncontrasting
confidence: 67%
“…Gardner et al have recently reported an association between climate factors and the appearance of virus in primary MERS-CoV cases [9]. The findings of this study may represent primary MERS-CoV cases.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…As well as seasonal calving, environmental factors have also been hypothesised to be associated with zoonotic transmission (measured as the incidence of primary human cases). Lower temperatures and humidity were found to be associated with higher numbers of reported primary human MERS cases in KSA (Gardner et al, 2019). Further investigation of potential seasonality has been highlighted as a priority by the FAO-OIE-WHO MERS-CoV Technical Working Group (FAO-OIE-WHO MERS-CoV Technical Working Group, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Factors that facilitate community transmission include lack of knowledge on transmission mechanisms, poor general hygiene practices and exposure to camels. Primary MERS-CoV human cases are also more likely to occur when conditions are relatively cold and dry [79].…”
Section: Community Transmissionmentioning
confidence: 99%